Combined aplasia of frontal and shenoid sinuses with hypoplasia of the maxillary sinus - Błochowiak, Katarzyna; Kamiński, Bartłomiej (Wydawnictwo Uniwersytetu Rzeszowskiego, 2018)
Introduction. Combined aplasia of multiple sinuses is extremely rare. Agenesis of the paranasal sinuses is an uncommon clinical condition that appears mainly in the frontal (12%) and maxillary (5-6%) sinuses. Case report. In this paper, we present the case of a 74-year-old woman with combined frontal and shenoid sinus aplasia accompanied by unilateral maxillary sinus hypoplasia. The findings were confirmed by a computed tomography scan of paranasal sinuses. The reason for admission was persistent headache, numbness of the left cheek and left alveolar process, and occasional nasal blockage. Discussion. The uniqueness of our case is that the patient is an elderly female with combined aplasia of the frontal and sphenoid sinus with hypoplastic maxillary sinuses, whereas previously reported cases were found in children and in young adults. Summary and conclusions. These anomalies can be misdiagnosed as chronic sinusitis or neoplasm. All potential sinus anomalies will have clinical implications and will hinder conventional and functional endoscopic sinus surgery.
Keywords: frontal sinus aplasia; maxillary sinus hypoplasia; paranasal sinus anomalies; paranasal sinus aplasia